Pemberdayaan Mayarakat Dusun Wates di Masa Pandemi Covid-19 Melalui Pelatihan Pembuatan Hand Santizer - Dhea Aulia Damayanti; Noor Rosyidah; Darma Taujiharrahman; Ratih Gabelni Adhi Nescha; Zakiyatur Rohmah; Wakhidatul Yulinar Rohmania; Hendri Hermawan Adinugraha (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2021)
The training for making hand sanitizers aims to train residents to maintain their health as much as possible while also utilizing the potential of this business during a pandemic. In addition, it also aims to provide socialization to the public regarding healthy behavior which will later become a new adaptation pattern during this pandemic. From the explanation above, the problem can be formulated: How was the training carried out? And how are their responses, abilities and obstacles in making hand sanitizers. The methods used are PAR (Participatory Action Research) and ABCD (Asset-Bassed Community Driven), where the dedication team goes directly to train by knowing the basic abilities of the participants. The implementation is carried out in several stages because it must pay attention to Health protocol, namely maintaining distance and not crowding. The results obtained in the training were that the participants felt happy and were able to make hand sanitizers while still writing the ingredients' recipes. Even though there are obstacles / obstacles, they can be overcome so that it is success.